Anilinopyrimidines: A Review Exploring Synthetic Approaches and Biological Activity - Pathak, Shilpi; Pandey, Rahul; Agrawal, Neetu (Letters in Organic Chemistry, 2023)
Anilinopyrimidines have a wide range of biological activities, including antibacterial, antifungal, and anticancer effects. They have a wide range of uses and opportunities due to their varied experimental preparation and study activities. This creates a lot of interest, experiments and analytical analyses are still being conducted to understand their medicinal chemistry better. According to their effects, which can include antifungal and antibacterial, anticancer or antitumor, and other properties, anilinopyrimidines are categorized in this review. In conclusion, it is critical to base the design of new anilinopyrimidine derivatives and the creation of novel synthesis methodologies on the most recent information discovered through recent research. This review intends to shed light on advancements in the synthetic and biological activity of analogs of anilinopyrimidines.
Keywords: synthesis